Identifikasi kesesuaian tata letak tanaman berdasarkan konsep Tri Mandala (studi kasus Pura Puseh lan Desa, Desa Pakraman Batuan dan Desa Pakraman Kebon Singapadu) - Widyastuti, I Gusti Ayu Agung Andari; Sugianthara, Anak Agung Gede; Semarajaya, Cokorda Gede Alit (Jurnal Arsitektur Lansekap; Vol.6, No.1, April 2020, 2020)
Temple is a shrine of Hindu religion and is one of the places for the application of traditional Balinese garden. Temples’s garden should use upakara plant that not only serves as a landscape element but also can be used as a means offering ( upakara ). The concept of plant placement in the temple’s garden should also characterize   the   local   philosophy ,  including   Tri Mandala . The purpose of this study is to identify plants   type   and   conformity   of plants placement  in   Pura Puseh lan Desa, Desa Pakraman Batuan  and   in  Pura Puseh Lan Desa,  Desa  Pakraman Kebon Singapadu based on Tri Mandala concept. The study uses survey methods with data collection techniques, through field observations, interviews, and library studies. The results showed that the two temples used upakara plants and ornamental plants as soft elements. The concept of plants placement is largely in accordance with the concept of Tri Mandala .